Educational practices in school health: an integrative review - Tatiane Marinz de Souza Luquez; Vera Maria Saboia (Universidad de Alicante, 2017)
The school is an important stage in participatory construction health reality, encouraging reflection and development of educational health promotion practices. The objective is to know the approaches that have guided the education of health promotion practices at school. This is an integrative review, to search in the databases LILACS, SCIELO, MEDLINE and PubMed. Guiding question: "What educational aspects have guided research on health education practices in scientific schools published in journals in the health area in the period 2005-2014?" Were included articles published in Portuguese, English and Spanish; in full; which reflect the theme, published and indexed in databases surveyed from 2005 to 2014. We selected 15 articles and analyzed in two categories: The training of teachers and the impact on the practice of school health; and Educational aspects present in the practice of school health. The practice of school health, still needs improvement in the actions of educators in the school health program. One can understand the need for new interventions appropriate to the reality of the students, considering socioeconomic and cultural aspects, environmental influences, behavioral and personal characteristics that are aimed at improving the quality of life and health of the school population.